Interleukin-1β-Induced Senescence Promotes Osteoblastic Transition of Vascular Smooth Muscle Cells - Linzi Han; Yuying Zhang; Mingming Zhang; Liyu Guo; Jun Wang; Fanjun Zeng; Deping Xu; Zongzhi Yin; Yuanhong Xu; Deguang Wang; Haisheng Zhou (Karger Publishers, 2020)
Introduction: Interleukin (IL)-1β, as a key biomarker and mediator of vascular calcification in patients with end-stage renal disease (ESRD), may be involved in the process of premature senescence of vascular smooth muscle cells (VSMCs). This work sought to investigate whether IL-1β-induced premature senescence contributes to the process of osteoblastic transition and vascular calcification in VSMCs. Methods: Eighty-eight patients with ESRD (aged 25-81 years), 11 healthy individuals, and 15 cases of lesion-free distal radial arteries from dialysis ESRD patients with angiostomy were collected in this study. Immunohistochemical analysis was performed to detect expression of IL-1β, p21, and bone morphogenetic protein-2 (BMP2) in the distal radial arteries. Primary human VSMCs from healthy neonatal umbilical cords were incubated with test agents for 1-3 days. Intracellular levels of reactive oxygen species (ROS) and senescence-associated-β-galactosidase (SA-β-gal) staining were used to detect senescent cells. Alizarin red staining and the calcium content of the cell layer were used to detect mineral deposition in VSMCs. Results: Coincident with positive staining of IL-1β, p21, and BMP2 in the lesion-free distal radial arteries, 66.67% patients showed mineral deposition. Serum IL-1β was 0.24 ± 0.57, 1.20 ± 2.95, and 9.41 ± 40.52 pg/mL in 11 healthy individuals, 20 patients without calcification, and 53 patients with calcification, respectively. Analysis of the cross-table chi-square test showed cardiovascular calcification is not correlated with levels of serum IL-1β in patients with ESRD (p = 0.533). In response to IL-1β, VSMCs showed a senescence-like phenotype, such as flat and enlarged morphology, increased expression of p21, an increased activity of SA-β-gal, and increased levels of ROS. IL-1β-induced senescence of VSMCs was required for the activation of IL-1β/NF-κB/p53/p21 signaling pathway. IL-1β-induced senescent VSMCs underwent calcification due to osteoblastic transition mainly depending upon the upregulation of BMP2. Resveratrol, an activator of sirtuin-1, postponed the IL-1β-induced senescence through blocking the NF-κB/p53/p21 pathway and attenuated the osteoblastic transition and calcification in VSMCs. Conclusions: High levels of IL-1β in medial smooth muscles of arteries may play roles in inducing senescence-associated calcification. IL-1β-induced senescence depending on the activation of the NF-κB/p53/p21 signaling pathway and contributing to osteoblastic transition of VSMCs.